Electroanalytical determination of zinc in human blood facilitated by acoustically assisted double extraction - Kruusma, J; Banks, C; Lust, E; Keis, H; Nei, L; Compton, R (2004)
The electroanalytical determination of zinc in human blood via an acoustically assisted double extraction technique is reported. First zinc(II) is rapidly extracted from diluted blood via complexation with diphenylthiocarbazone in chloroform through acoustic emulsification of the two phases. After insonation the bulk phases reform and the metal is back extracted by emulsifying with electrochemically clean aqueous acid and the zinc quantified via anodic stripping voltammetry, giving close agreement to the blind independent AAS analysis. The double extraction method is effective since species that otherwise interfere with the direct ASV determination either remain in the initial aqueous phase, or are transferred to the organic phase, but are unlikely to be doubly transferred so producing a 'clean' final aqueous medium for ASV.